The Twenty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2004)

The Twentieth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2001)

The Twenty-First Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2002)

The Twenty-Second Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2003)

The Twenty-Fourth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2005)

The Twenty-Fifth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2006)

The Twenty-Sixth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2007)

The Twenty-Seventh Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2008)

The Twenty-Eighth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2009)

The Twenty-Ninth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2010)

The Thirtieth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2011)

The Thirty-First Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2012)

The Thirty-Second Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2013)

The Thirty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2014)

The Thirty-Fourth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2015)

2016-17 Annual Report - The English Speaking Catholic Council (ESCC) (2017)

Annual Report 2017-18 - The English Speaking Catholic Council (ESCC) (2018)

Annual Report 2018-19 - The English Speaking Catholic Council (ESCC) (2019)

Strategic Plan : 2005-2006 to 2008-2009 - The English Speaking Catholic Council (ESCC) (2005)

Strategic Plan : 2011-2016 - The English Speaking Catholic Council (ESCC) (2010)

Brief : Submitted to the Federal Parliamentary Committee on Palliative and Compassionate Care by the English-speaking Catholic Council - The English Speaking Catholic Council (ESCC) (2010)
The English Speaking Catholic Council acknowledges with deep gratitude the invaluable contribution of the principal authors of this brief: Dr. Ramona Coelho, a family physician who works at CLSC Metro in Montreal. Her training included a focus in palliative care. She spends half of her practice caring for disabled and frail elderly persons who are homebound. And Daniel Cere, Ph.D., Professor, Faculty of Religious Studies, McGill University, and member of the Board of the ESCC. The English Speaking Catholic Council is pleased to present this Brief to the Federal Parliamentary Committee on Palliative and Compassionate Care.

Reasonable Accomodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)

Directives on Daycares - The English Speaking Catholic Council (ESCC) (2011)

Statement Regarding the Situation of the Catholic Times - The English Speaking Catholic Council (ESCC) (2010)

Ethical Guidelines Handbook for the Catholic Laity in Apostolic Service - The English Speaking Catholic Council (ESCC) (2007)

Statement on Bill 40 : An Act to Amend the Education Act Principally with Respect to School Organization and Governance - The English Speaking Catholic Council (ESCC) (2019)

General Consultation and Public Hearings on Bill 60 - The English Speaking Catholic Council (ESCC) (2013)
The English Speaking Catholic Council (ESCC) objects to the proposed “Charter,” Bill 60, on the following grounds: • It threatens to erode the historically and legislatively foundational freedoms of conscience, religion, opinion and expression. These are considered to be “first” freedoms in our society and any trend to dilute or undermine these freedoms must be resisted. • It proposes a secularized society in which religious expression and practice are marginalized. It seeks to reframe the public discussion so that the exercising of Charter-protected rights is to be understood as an imposition upon society which requires the permission of the State. • It muddies the separation of Church and State as it proposes the State has the power to define the nature of religious belief, practice and expression. • In all of the aforementioned points the role of the State is elevated above the proper parameters of a democratically elected and responsible government. The ESCC calls upon the Government of Quebec to withdraw Bill 60.

Consultation générale et auditions publiques sur le projet de loi n° 60 - The English Speaking Catholic Council (ESCC) (2013)
Le Conseil catholique d'expression anglaise (CCEA) s’oppose à la charte proposée par le projet de loi 60, et ce, pour les raisons suivantes : • Il menace d’éroder, d’un point de vue historique et juridique, les libertés fondamentales de conscience, de religion, d’opinion et d’expression. Il s’agit des libertés « primordiales » dans notre société et il faut s’opposer à tout ce qui tend à diluer ou à réduire ces libertés. • Il propose une société sécularisée dans laquelle l’expression et la pratique religieuses sont marginalisées. Il cherche à recadrer le débat public de manière à ce que l’exercice des droits et libertés protégés par les chartes soit perçu comme imposé à la société et nécessitant la permission de l’État. • Il formule une notion embrouillée de la séparation de l’Église et de l’État en proposant que l’État a le pouvoir de définir la nature des croyances, de la pratique et de l’expression religieuses. • Dans tous les points susmentionnés, il situe le rôle de l’État au-dessus des paramètres de gouvernance appropriés d’un gouvernement élu démocratiquement et responsable. Le CCEA demande au gouvernement du Québec de retirer le projet de loi 60.

Reasonable Accommodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)
We agree with the Commission that “the management of diversity, especially religious diversity... appears above all to pose a problem.” The appearance of a problem seems to have been provoked in large measure by post 9/11 “alarmist media coverage.” Careful reflection will show that there is no problem in reality and that the alarm is not worthy of Quebecers. The ESCC therefore counsels strongly against the temptation to tamper with the current constellation of relevant rights and privileges in Quebec; it is a product of the unique evolution of Quebec society and functions well as “a fair, original model of collective life of which we are proud.”

Accommodements raisonnables et liberté de religion au Québec - The English Speaking Catholic Council (ESCC) (2007)
We agree with the Commission that “the management of diversity, especially religious diversity... appears above all to pose a problem.” The appearance of a problem seems to have been provoked in large measure by post 9/11 “alarmist media coverage.” Careful reflection will show that there is no problem in reality and that the alarm is not worthy of Quebecers. The ESCC therefore counsels strongly against the temptation to tamper with the current constellation of relevant rights and privileges in Quebec; it is a product of the unique evolution of Quebec society and functions well as “a fair, original model of collective life of which we are proud.”

Reasonable Accomodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)

Report on the Proposed Ethics and Religious Culture Program - The English Speaking Catholic Council (ESCC) (2006)
We affirm the positive objectives of this program, namely: 1) To incorporate ethics and religion into public education; 2) To foster students’ capacity to know and express their moral and religious convictions within a pluralistic context; 3) To develop the capacity for meaningful dialogue about diverse moral and religious convictions; 4) To anchor this program in the distinctive cultural and religious heritage of Quebec. However, we recommend some major revisions to the program. Five interrelated areas stand out for us.

Freedom of Religious Instruction : A Fundamental Right of Parents and Children - Murphy, Martin P.; The English Speaking Catholic Council (ESCC) (The English Speaking Catholic Council (ESCC), 2008)
From the time it was proposed in the late 19809s to shift the Quebec school system from a denominational model to a linguistic one, the English Speaking Catholic Council (ESCC) has consistently fought for freedom of religion and parental choice in religious instruction for people of all faiths. Time and again, the ESCC has defended these principles in its submissions to the National Assembly, the Commission for the Estates-General on Education, the Special Joint Committee of the House of Commons and the Senate, and most recently, the BouchardTaylor Commission on Reasonable Accommodation of Minorities.